Study of solution towards ground leakage current via inverter switching in different topologies for grid connected PV system - Kimpol, Norhanisa (2013)
Renewable energy sources are major issues in order to address the energy problem. Among them, the PV (Photovoltaic) system will be dominant because its availability and reliability. One of the common problems that arise due to the formation of solar PV panels is capacitive ground current. Although transformer helps in reducing this problem, the poor side of having the transformer in PV systems is accounted to bulky in size and hard to install the entire PV system. Indirectly, the cost is higher and led to a lower efficiency due to higher losses of power. To solve this, transformerless inverter topology offers a solution for the efficiency, size and weight. The leakage current depends on both inverter topology and control strategy. In this report, different inverter topologies have been reviewed with respect to ground current formation due to inverter switching that causes varying common mode voltage that will excite the resonant circuit as well as causes the leakage current phenomenon. The transformerless inverter topologies that are considered are Bipolar H-Bridge, Modified HB-ZVR and NPC. In order to study the effect of having a transformer in eliminating the ground current, Bipolar H-Bridge inverter with transformer also include in this project. All proposed topologies are modelled and simulated to compare the pattern and behavior of ground leakage current with other existing topology. By comparing the pattern of the output from the simulation, a conclusion is given which proves that NPC topology are suitable for PV application due to low leakage current compared with other two topologies.